Budidaya Lamtoro Sebagai Bank Pakan Sumber Protein di Kecamatan Moyo Utara Kabupaten Sumbawa - Oscar Yanuarianto; Muhamad Amin; Syamsul Hidayat Dilaga; Dahlanuddin Dahlanuddin (Jurnal Gema Ngabdi, 2021)
: Currently, the Lamtoro plant has become the prima donna of forage for ruminants in NTB Province. This plant is able to grow in relatively dry land and can be a source of protein for ruminants, maintenance and maintenance is relatively easy because it does not require a lot of water. On the other hand, the use of lamtoro as a source of protein for ruminant feed is an efficient step in meeting animal feed needs. Through the utilization of lamtoro, the use of less productive land can be utilized as well as a reforestation tree to prevent erosion, on the other hand, the use of lamtoro can increase farmers' income because the cost of foraging for food in the dry season can be minimized, the quality of feed given to livestock is maintained so that livestock productivity is maintained. The dry season remains high, therefore the Maju Bersama Group in the Filter Village of North Moyo District as one of the livestock groups in North Moyo District where the population does a lot of raising ruminant livestock, it is deemed necessary to carry out community empowerment service activities through counseling on “Lamtoro Cultivation As a Protein Source Feed Bank in North Moyo District, Sumbawa Regency. " Providing counseling in the form of demonstrations, speeches (lectures and questions and answers), and distribution of leaflets attended by 20 participants including members of farmer groups and local residents. The results of the counseling were considered very useful. This could be seen from the enthusiasm of the extension participants who attended both the question and answer session and the demonstration session. The output of this counseling result is an ISSN service journal and a brochure